Evolution of Land Policy for Landslide Risk Reduction in Quito - PUENTE-SOTOMAYOR, Fernando; VILLAMARIN-JURADO, Paulina; CEVALLOS, Luis Andrés (Revista INVI, 2023)
Quito's 2011 urban plan incorporated the zoning "Landslide Risk Zones", banning new buildings. This policy, with weak technical backing, had inaccuracies that impacted households’ safety and their economies. After ten years of implementation and reforms, this policy still does not solve the problem. This analysis proposes lessons for the future and for similar contexts. This case study reviewed plans, urban regulations, and municipal studies on landslide risk since 1990. This input was triangulated with interviews with municipal officials and the analysis of land management data. To contrast this, layers of risk zones, the 2005-2017 period events, and areas highly susceptible to landslides were spatially overlaid. For ten years, 81% (644 hectares) of highly hazardous areas were not protected as risk zones, leaving risk generation unchecked. Conversely, 25% (218 hectares) of the risk zone area did not present high susceptibility to landslides, affecting landowners. Recently, the 2021 urban plan updated an affectation layer of 260 thousand hectares of the highest landslide-susceptible areas in Metropolitan Quito, where only 27% of the 2005-2017 events coincided with this highest landslide-susceptible areas. This latest plan opens the possibility of specifying preventive planning with planning instruments for smaller territory scales, and a master plan for risk management is expected. The 2011 zoning for landslide risk prevention, the objective of which was landslide risk reduction, had inaccuracies that left territories with high landslide-susceptibility unprotected, and affected the owners of risk-free properties. Although there were mid-term studies with better results, the policy was not updated until 2021. However, the new layer barely covers 27% of the damaged sites, and future plans of smaller city scales are scheduled to detail the risk zoning, while more events continue to occur, with extreme climatic variability becoming more frequent.